Tethered imidazole mediated duplex stabilization and its potential for aptamer stabilization. Issue 22 (10th November 2018) - Verdonck, Lars; Buyst, Dieter; de Vries, Anne-Mare; Gheerardijn, Vicky; Madder, Annemieke; Martins, José C
Abstract: Previous investigations of the impact of an imidazole-tethered thymidine in synthetic DNA duplexes, monitored using UV and NMR spectroscopy, revealed a base context dependent increase in thermal stability of these duplexes and a striking correlation with the imidazolium p K a . Unrestrained molecular dynamics (MD) simulations demonstrated the existence of a hydrogen bond between the imidazolium and the Hoogsteen side of a nearby guanosine which, together with electrostatic interactions, form the basis of the so-called p K a -motif responsible for these duplex-stabilizing and p K a -modulating properties. Here, the robustness and utility of this p K a -motif was explored by introducing multiple imidazole-tethered thymidines at different positions on the same dsDNA duplex. For all constructs, sequence based expectations as to p K a -motif formation were supported by MD simulations and experimentally validated using NOESY. Based on the analysis of the p K a values and melting temperatures, guidelines are formulated to assist in the rational design of oligonucleotides modified with imidazolium-tethered thymidines for increased thermal stability that should be generally applicable, as demonstrated through a triply modified construct. In addition, a proof-of-principle study demonstrating enhanced stability of the l -argininamide binding aptamer modified with an imidazole-tethered thymidine in the presence and absence of ligand, demonstrates its potential for the design of more stable aptamers.